Impact of Corona Pandemic (Covid-19) on the Conduct of Criminal Investigation - et.al, Sherifa Fouad Mustafa, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A criminal case is considered the means by which everyone who has empowered himself to violate the law and order and to be exposed to the security, stability, and interests of society, and through it the prosecution of its perpetrator and all who participated in it to impose the appropriate penalty for each of them, and the criminal case is governed by procedural rules in which the authorities determine their powers and the procedures to be followed In investigating and controlling crimes, collecting evidence, prosecuting whoever came to it or whom it was attributed to and adjudicating them, through the stages that the case goes through, and these rules are codified in the Criminal Procedure Law. In addition, the criminal procedures witnessed a qualitative shift in the Kingdom of Bahrain in light of the exceptional circumstances that the countries of the world are experiencing in the outbreak of the emerging coronavirus (Covid-19), and because of these circumstances, the Kingdom of Bahrain has taken precautionary measures to limit the spread of the virus and protect individuals and their interests, and accordingly, the Bahraini legislator amending some provisions of the Criminal Procedure Law, which in turn affected the course of the criminal case, and the most important of these amendments are embodied in the replacement of the traditional method known from the moment the criminal case is initiated, which is to confront the perpetrator face to face, with a modern technological method in which there is a remote confrontation through technologies and devices. Visual and audio within the framework of the implementation of precautionary measures. If this indicates anything, then it indicates the Kingdom's keenness to address such obstacles, which in turn may affect the public interest, but thanks to the integration of modern technologies through virtual innovation, the Kingdom will witness a qualitative leap in the future in dealing with such exceptional circumstances, which in turn it will change the structure of many areas, the most important of which is the legal interface